Biometry and pathological ultrasound findings in multiple pregnancies - Yuly Natalia Guzmán Yara; Montserrat Uriel Calvo; Sandra Liliana Beltrán; Liliana Bandera; José de la Hoz-Valle; Ximena Carolina Romero (Instituto Materno Infantil de Pernambuco, 2023)
Resumo Objectives: to determine the prevalence of pathological findings according to the type of chorionicity in pregnancies in two institutions in Bogotá, Colombia. Methods: descriptive, retrospective, cohort study. Biometric variables were calculated, and pathological findings were evaluated according to the type of chorionicity in multiple pregnancies. Statistical characterization was performed with absolute frequencies, calculation of relative frequencies in qualitative variables, standard deviation measures, median and interquartile range. In addition, a descriptive analysis of the information was carried out. Results: 528 studies were carried out in 141 pregnant women, 98.5% (n = 139) twins and 1.4% (n = 2) triplets. A prevalence of 35.4% of fetal complications was calculated. The most frequent was fetal growth restriction (p=0.37). According to each type of chorionicity, fetal growth restriction was presented in 50% (1/2) of the trichorionics, 16.6% (7/42) of the monochorionics, and 11.3% (11/97) of the dichorionics. Conclusion: fetal growth restriction was the most common finding, both in trichorionics, monochorionics and dichorionics pregnancies.